MANAJEMEN MUTU TENAGA PENDIDIK DI MADRASAH IBTIDAIYAH NW TANAK MIRA WASANABA LAUK - Hully Hully; Lale Yaqutunnafis; Irwan Irwan (KOLONI, 2022)
Quality management of teaching staff is the ability to manage human resources and other resources and function them according to their respective areas of expertise in a systematic, effective and efficient manner. This research method uses qualitative research with data collection techniques using interviews, observation and documentation. Data analysis was carried out in three stages, namely data reduction, data display and conclusion drawing. The validity of the data is done by conducting in-depth observations, extending the presence of researchers, adequacy of references and triangulation. The results of this study indicate that the quality management of teaching staff at Madrasah Ibtidaiyah NW Tanak Mira Wasanaba Lauk is carried out with careful planning such as formulating priority programs and goals to be achieved, organizing in accordance with their respective areas of expertise maximally, effectively and efficiently. In management it is also carried out to fulfill educator standards such as educational qualifications and also carry out supervision in order to produce quality education. thus it can be concluded that the quality management of teaching staff is very important in order to produce better and quality education. Keywords: Management, Quality, Educators